STUDI KASUS EDEMA FISIOLOGIS PADA IBU HAMIL DI PUSKESMAS GEMPOL - Rita Agustiningrum; Nurul Azizah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
Swelling of the legs during pregnancy is common and can be caused by physiological or pathological factors. This case study aims to explore the causes, symptoms, and treatment of physiological edema in pregnant women, emphasizing the importance of obstetric care. This case study was conducted at the Gempol Community Health Center with the subject Mrs. R, a 31year old pregnant woman who experienced physiological edema. Data was collected through observation, structured interviews, and physical examination. The methods used include observing daily activities, interviews to collect qualitative data, and physical examination to measure the level of leg swelling. Obstetric care involving lifestyle changes and education significantly reduced leg swelling, demonstrating a positive impact on the patient's condition. Important findings from gab research show that light exercise such as pregnancy exercise and soaking the feet in warm water significantly reduces the degree of edema in pregnant women in the second and third trimesters. Appropriate obstetric care can effectively manage physiological edema during pregnancy, ensuring better health outcomes for mother and baby.